The Novel of Chitosan-Hydroxyapatite of Chicken Eggshells Composite as Methylene Blue Adsorbent - Arthika Putri, Nur; Ramadani, Kurnia; Chadijah, Sitti; Rasyid, Firnanelty (Universitas Andalas, 2026)
High egg consumption in Indonesia, particularly in South Sulawesi, presents a significant opportunity to utilize eggshells as precursors for hydroxyapatite. This study aims to characterize hydroxyapatite derived from chicken eggshells and to evaluate the absorption properties of chitosan-hydroxyapatite composites for methylene blue removal. The precipitation method was used for hydroxyapatite synthesis, as it produces hydroxyapatite with a high level of purity and low contamination. X-ray diffraction (XRD) analysis revealed that eggshells contain approximately 30% CaCO₃. The XRD diffractogram of hydroxyapatite from eggshells showed a peak at 2θ = 31.94º. Fourier-transform infrared (FTIR) spectroscopy identified key functional groups in hydroxyapatite, including hydroxyl (-OH) at 3434 cm⁻¹, carbonate (-CO₃²⁻) at 1421 cm⁻¹, phosphate bending (-PO₄³⁻) at 565 cm⁻¹, and phosphate stretching (-PO₄³⁻) at 1035 cm⁻¹. The chitosan-hydroxyapatite (Cs-HAp) composite showed the incorporation of chitosan functional groups, including amine (-NH) at 1577 cm⁻¹ and methylene (-CH) at 2928 cm⁻¹. The chitosan-hydroxyapatite composite demonstrated effective removal of methylene blue dye, with an absorption efficiency of 96% at a Cs-HAp ratio of 2:2 within 180 minutes. Based on the high adsorption efficiency, the chitosan-hydroxyapatite composite shows great potential for absorbing methylene blue.